Concise Review: Extracellular Vesicles Overcoming Limitations of Cell Therapies in Ischemic Stroke. (23rd September 2017) - Doeppner, Thorsten R.; Bähr, Mathias; Hermann, Dirk M.; Giebel, Bernd
Abstract: Despite recent advances in stroke therapy, current therapeutic concepts are still limited. Thus, additional therapeutic strategies are in order. In this sense, the transplantation of stem cells has appeared to be an attractive adjuvant tool to help boost the endogenous regenerative capacities of the brain. Although transplantation of stem cells is known to induce beneficial outcome in (preclinical) stroke research, grafted cells do not replace lost tissue directly. Rather, these transplanted cells like neural progenitor cells or mesenchymal stem cells act in an indirect manner, among which the secretion of extracellular vesicles (EVs) appears to be one key factor. Indeed, the application of EVs in preclinical stroke studies suggests a therapeutic role, which appears to be noninferior in comparison to the transplantation of stem cells themselves. In this short review, we highlight some of the recent advances in the field of EVs as a therapeutic means to counter stroke.